Sosialisasi dan Pelatihan Tata Kelola Administrasi Pemerintahan Kelurahan Batunadua Jae Padangsidimpuan - Indra Syahputra Marpaung; Tri Eva Juniasih; Rina Tiur Lona; Nurbaya Harianja (Jurnal Pengabdian kepada Masyarakat Radisi, 2021)
Good urban village administration governance in developing its territory is that the governance that regulates villages/kelurahan must uphold transparency, accountability, responsibility, independence and equality/fairness and adhere to the applicable rules and procedures. Good urban village administration will be a supporting factor in the development of the village and the welfare of the village community he leads. This community service is one of the implementations of the Tri Dharma of Higher Education in the form of socialization and training on administrative governance in Batunadua Jae Village, Batuandua Padangsidimpuan District, Padangsidimpuan City. The purpose of this service activity is to improve the ability and understanding of employees in managing and carrying out their duties and functions, especially in community services so that village development in the kelurahan area can be realized evenly. Based on the results of the evaluation, it was concluded that there was an increase in the attitude of employees in serving the public, the ability to carry out governance of government administration both in public service and in using computers had increased.